论老舍小说中的“忍” - 刘, 玲 (2023)
老舍是中国现代著名作家。20 世纪 30 年代初，以小说创作步入文坛。他的小说重在表现市民阶层的命运与性格，并从独特的“文化”视角向世人展现了一个五光十色的市民世界。本文以老舍的小说为中心，以人物的“忍”为切入点，探讨老舍如何刻画市民阶层的命运与性格，以此理解老舍小说中人物性格复杂丰富的内涵。 全文共分为五个部分。第一部分简单介绍老舍的背景及前人研究的现状，并界定“忍”的概念。第二部分从老舍早期与中后期小说中，挑选具有代表性的人物与情节，梳理老舍小说中人物“忍”性格的形成与发展过程。前期老舍在小说中只是着墨不多地写个体的“忍”；中后期则既写个体的“忍”又写群体的“忍”，有一个逐步深化的过程；第三部分从老舍的母亲与儒家思想、佛教思想等因素入手，探索老舍小说中对人物“忍”的描写如此之多的原因。发现老舍小说中的“忍”受母亲软而硬性格与儒家的“仁”、“礼”、“和”思想与佛教的“忍辱”思想等因素的影响。第四部分挑选老舍小说中与“忍”有关的人物与情节，做细致的归类与分析，将小说中人物“忍”的类型分为：平民阶层的负重型忍、中层阶级的修身型忍、丑类人物的防御型忍、女性人物的随机型忍四种，总结出不同人物“忍”的原因与目的。第五部分为结论，通过对全文的回顾，发现老舍对“忍”的态度既赞扬又批判。他赞扬“忍”所透露出的积极意义，夸赞“忍”中涵盖的自强不息与拼搏向上的精神，同时又批判“忍”的消极方面，认为“忍”造成民众精神的麻木与国家的退步。老舍是一位现实主义作家，分析老舍小说中的“忍”，有利于更深入地了解老舍的思想，对全面理解老舍及其作品具有重要作用。Lao She is a famous modern Chinese writer. In the early 1930s, he enteredthe literary world through novel creation. His novels focus on portrayingthefate and character of the common people, and froma unique "cultural"perspective, present a colorful world of citizens to the world. This thesis takesLao She's novels as the center and the "tolerance" of the characters as thestarting point to investigate how Lao She portrays the fate and character of thecommon people in order to understand the complexities and rich connotationsof the characters' personalities in Lao She's novels. This thesis divided into five parts. The first part briefly introduces thebackground of Lao She and the current status of previous research, anddefinesthe concept of "tolerance". The second part selects representative charactersand plots from Lao She's early and mid to late novels, and sorts out theformation and development process of the character's "tolerance" character inLao She's novels. In the early stage, Lao She only wrote about the individual's"tolerance" with limited attention in her novels; In the middle and later stages, both the individual's "tolerance" and the group's "tolerance" were written, witha gradual deepening process; The third part starts with Lao She's mother andexternal factors such as Confucianism and Buddhism, exploring the reasonswhy there are so many descriptions of character "tolerance" in Lao She's novels. It was found that the "tolerance" in Lao She's novels is influenced byfactorssuch as the mother's soft and hard personality, the Confucian ideasof"benevolence", "etiquette", "harmony", and the Buddhist thought of "enduring humiliation". The fourth part selects the characters and plots relatedto"tolerance" in Lao She's novels, and conducts a detailed classificationandanalysis. The types of characters' "tolerance" in the novels are divided intofourtypes: burden bearing tolerance of the common class, self-cultivation toleranceof the middle class, defensive tolerance of ugly characters, and randomtolerance of female characters. The reasons and purposes for different characters' "tolerance" are summarized. The fifth part is the conclusion. Through a review of the entire text, it is found that Lao She's attitude towards"tolerance" is both praise and criticism. He praised the positive significancerevealed by "tolerance", praised the spirit of self-improvement andstrivingupward contained in "tolerance", and criticized the negative aspectsof"tolerance", believing that "tolerance" causes the numbness of the people'sspirit and the regression of the country. Lao She is a realist writer. Analyzing the "tolerance" in Lao She's novelsis conducive to a deeper understanding of Lao She's thoughts and playsanimportant role in a comprehensive understanding of Lao She and her works.